Bioactivity Potential of Aesculus hippocastanum L. Flower: Phytochemical Profile, Antiradical Capacity and Protective Effects on Human Plasma Components under Oxidative/Nitrative Stress In Vitro - Aleksandra Owczarek; Joanna Kołodziejczyk-Czepas; Paulina Marczuk; Julia Siwek; Katarzyna Wąsowicz; Monika Anna Olszewska (MDPI AG, 2021)
Horse chestnut (Aesculus hippocastanum) flower is a traditional medicine applied to alleviate symptoms of chronic venous insufficiency (CVI). However, its flavonoid-based composition has not been sufficiently recognized, and the data supporting its traditional application are lacking. In the work, 43 constituents were detected by UHPLC-PDA-ESI-TQ-MS/MS (flavonoids, phenolic acids, flavanols, and coumarins), including 31 reported in the flower for the first time. The quantitative HPLC-PDA study (developed and validated for quality control purposes) indicated the fractionated extraction as an efficient method for enhancing the total polyphenol content (TPHC) in the extracts (up to 414.06 mg/g) and kaempferol glycosides as their dominant constituents (75.05-82.14% TPHC). The activity studies showed significant scavenging properties of the extracts and their constituents towards reactive oxygen species (especially against highly reactive hydroxyl radical, with capacities up to 7.85 mmol ascorbic acid equivalents/g). Moreover, the analytes relevantly protected human plasma biomolecules from peroxynitrite-induced oxidative/nitrative damage; at 1-50 µg/mL, they hindered the protein nitration and lipid peroxidation, decreasing the levels of 3-nitrotyrosine (by up to 50%) and thiobarbituric acid reactive substances (by up to 70%), respectively. The extracts also averted the depletion of plasma thiols (by up to 67%) and improved the non-enzymatic antioxidant capacity of plasma. The demonstrated mechanisms might be partly responsible for the efficacy of the flower in CVI. Additionally, the anti-aggregatory and anticoagulant properties of the extracts were found only mild or negligible, which suggests that they may be safely applied with drugs impacting the coagulation process.